The Combined Effects of Cadmium and Microplastic Mixtures on the Digestion, Energy Metabolism, Oxidative Stress Regulation, Immune Function, and Metabolomes in the Pearl Oyster (Pinctada fucata martensii) - Jiaying Yao; Zixin Gao; Zhixiang Wang; Zhanbo Ge; Yujing Lin; Luomin Huang; Jiaen Liu; Heqi Zou; Chuangye Yang; Robert Mkuye; Yuewen Deng (Fishes)
The accumulation of cadmium (Cd) and microplastics (MPs) can have major deleterious effects on the health of marine ecosystems and organisms, including the pearl oyster Pinctada fucata martensii. Here, we characterized the effects of Cd and MPs on key biochemical parameters of P. f. martensii via an experiment with various treatments. Pearl oysters were exposed to either only Cd (5 or 50 μg/L), only MPs (5 mg/L), or both Cd and MPs for 2 d, and this was followed by a 5-day recovery period. Measurements of the activities of lipase, amylase, protease, T-ATPase, catalase, glutathione peroxidase, acid phosphatase, and alkaline phosphatase enzymes, as well as the malondialdehyde content in the hepatopancreas, were made at various time points during the experiment. Metabolomics analysis of the gills was also performed. Significant interactions between time and treatment on lipase, protease, and catalase activities were observed. However, no significant effect of time–treatment interactions on amylase and T-ATPase activities was observed. Enzyme activities varied among groups both during the exposure period (6 to 48 h) and the recovery period. The malondialdehyde content was also increased throughout the experiment. Pathway analysis indicated that the purine metabolism, glycerophospholipid metabolism, nucleotide metabolism, arachidonic acid metabolism, neuroactive ligand–receptor interaction, and linoleic acid metabolism pathways were the most commonly affected under different treatments. The findings of our study revealed the differential effects of exposure time and treatment on enzyme activities and metabolites and their respective pathways. Our findings enhance our understanding of the biochemical responses of the pearl oyster P. f. martensii to environmental stressors, particularly Cd and MPs.